The organization model of socio-cultural practices of youth enrichment programs (as exemplified by a student ball) - Maxim V. Ivanov (Saratov State University, 2021)
The article presents the results of the theoretical analysis of such phenomena as "socio cultural practices", "enrichment program". The research determines their role in students' personal development. The contemporary social position of a student calls for a new pedagogical approach, and therefore requires innovative or retro-innovative approaches. The author develops a socio-cultural practice of the youth enrichment program merging the ball and the role-play. Thus, the research aim is to develop an organization model of socio-cultural practices of youth enrichment programs (as exemplified by a ball) in order to enable students' personal development. The study reveals characteristic pedagogical features of the socio-cultural practices of youth enrichment programs. Using the example of a student ball, the article shows how through the study of the history of dance and etiquette, students immerse themselves in the cultural environment, which will contribute to the development of patriotism, diligence and curiosity. Team work on concert acts contributes to the formation and strengthening of student partnership. Discussions about the nature of politeness promote kindness, empathy, honesty, and courtesy in student relationships. Students also develop non-standard thinking. Working together in the youth enrichment program, students learn to be hard-working and creative. Part of the enriching experience of this socio-cultural practice is secured in the non-standard situation that goes beyond students' usual everyday life. The practical application of the research results makes it possible to use the proposed model to develop socio-cultural practices of youth enrichment programs aimed at students' personal development.